The impact of TikTok user satisfaction on continuous intention to use the application - Abdel-Aziz Ahmad Sharabati; Shafiq Al-Haddad; Mohammad Hamdi Al Khasawneh; Natalie Nababteh; Mai Mohammad; Qais Abu Ghoush (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
People use social media not only for social purposes but also for business purposes. It is used in management and marketing as a tool to manage organizations and market products and services, especially to influence customers' intention and satisfaction. Therefore, the research purpose is to define factors that influence continuous intention to use TikTok in Jordan and to what extent satisfaction with TikTok influences continuous intention to use TikTok. The current research uses a quantitative cross-sectional approach. Data was collected by online surveys and shared on several social media sites such as WhatsApp, Instagram, and Facebook. A total of 402 responses were valid for further analysis. Then, Structural Equation Modeling (SEM) was performed. The results indicate that the following factors significantly affect satisfaction: self-expression, informativeness, a sense of belonging, and trendiness in TikTok. However, the following factors do not significantly affect satisfaction: sociability, affection in TikTok, and past time in TikTok. The factors can explain 48.5% of satisfaction. Finally, satisfaction has a positive significant influence on users' continuous intention to use TikTok and can explain 30.6% of the user's continuous intention to use TikTok. In conclusion, the organizations have to heavily use the factors that influence the users' satisfaction to increase users' continuous intention.
Keywords: 650; continuous intention; Jordan; social media; TikTok; user satisfaction